PENGARUH KREDIBILITAS TERHADAP NIAT BELI MELALUI MEDIA SOSIAL YANG MEDIASI SIKAP PENGGUNA DAN DI MODERASI INFLUENCER FOLLOWER - Risma Rifatul Koirunisa; Rini Kuswati (POLITEKNIK LP3I JAKARTA, 2025)
This study aims to explain the effect of credibility on purchase intention through social media mediated by user attitudes and moderated by influencer followers. Sampling in this study used a nonprobability sampling technique with a purposive sampling method. Sample collection used a questionnaire with a Likert scale. The population of this study were active social media account users with active Instagram accounts. with the number of respondents obtained 150 people. The results showed that Influencer Followers and Influencer Credibility have a positive and significant influence on consumer Purchase Intention. This finding shows the importance of building trust and involvement in influencer-based marketing strategies. Meanwhile, the interaction between Influencer Followers and User Attitudes towards Purchase Intention did not show a significant effect. Thus, it can be concluded that the direct influence of Credibility and influencer follower involvement is more dominant in forming purchase intention than the indirect path or interaction between variables in this model.